Carol Wayne White, Black Lives and Sacred Humanity: Toward an African American Religious Naturalism. (2nd May 2019) - Carter, Christopher
Abstract : Carol Wayne White, Black Lives and Sacred Humanity: Toward an African American Religious Naturalism (New York: Fordham University Press, 2016), 132 pp., $25.00 (pbk), ISBN: 978-0-8232-6982-2.